The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1517-3151.0546
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and evaluation of human exposure to vibration transmitted to hand-arm system during leisure cyclist activity

Abstract: The cycling activity has increased in recent years, either as a means of leisure or physical activity or as means of transport. Discomfort is one of the main complaints for cyclists, especially when related to the type o pavement they use while riding. This work presents a study of measurement and evaluation of human exposure to hand-arm vibration in the leisure cyclist activity in different pavements in order to classify according to vibration discomfort and to vibration injury risk. Methods: Vibration measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The measurement and evaluation of human exposure to hand-arm vibration in relation to the pavement surface type has been examined in previous literature. Gomes and Savionek (2014) conducted hand-arm vibration exposure on three pavement surface types: asphalt, precast concrete and interlocking concrete blocks. Using a tri-axial piezoelectric accelerometer fixed to the handle bars, daily exposure to vibration (A(8)) for a daily duration of exposure of two hours (T=2 hrs) was considered to represent an average exposure time for leisure cycling purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The measurement and evaluation of human exposure to hand-arm vibration in relation to the pavement surface type has been examined in previous literature. Gomes and Savionek (2014) conducted hand-arm vibration exposure on three pavement surface types: asphalt, precast concrete and interlocking concrete blocks. Using a tri-axial piezoelectric accelerometer fixed to the handle bars, daily exposure to vibration (A(8)) for a daily duration of exposure of two hours (T=2 hrs) was considered to represent an average exposure time for leisure cycling purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results showed that the handlebar and fork were the main contributors of vibration induced at the hands, whilst the frame and wheels were the main components associated with vibration induced at the buttocks of the cyclist (Lépine et al 2015). Gomes and Savionek (2014) conducted hand-arm vibration exposure assessment on a range of pavement surfaces including asphalt, precast concrete and interlocking concrete blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum input acceleration over the course of measurement was 5 m/s 2 , which is far below the safe threshold defined by International Standard Organization (ISO 5349-1:2011) for exposure to vibration for less than 5 min. [ 26 ]. The transverse movement of the shaker head relative to the skin was constrained using a three-dimensional (3D) printed component, fixed on the tibia with an elastic band, minimizing the effects of lateral motion [ 18 ].…”
Section: Methodsmentioning
confidence: 99%